2016
DOI: 10.5194/ars-14-175-2016
|View full text |Cite
|
Sign up to set email alerts
|

Delayed response of the global total electron content to solar EUV variations

Abstract: Abstract. The ionospheric response to solar extreme ultraviolet (EUV) variability during 2011–2014 is shown by simple proxies based on Solar Dynamics Observatory/Extreme Ultraviolet Variability Experiment solar EUV spectra. The daily proxies are compared with global mean total electron content (TEC) computed from global TEC maps derived from Global Navigation Satellite System dual frequency measurements. They describe about 74 % of the intra-seasonal TEC variability. At time scales of the solar rotation up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…In earlier studies, the correlation of the ionospheric delay has been calculated for different ionospheric parameters based on daily and hourly resolutions, as shown in Table 1. For example, Jakowski et al (1991) used the solar radio flux index F10.7 and calculated a delay of 1-2 d. Jacobi et al (2016) confirmed this delay with satellite-based EUV-TEC measurements (Unglaub et al, 2011) and also calculated the ionospheric delay with EUV fluxes. The validation with EVE flux measurements was important because the solar rotation variations of F10.7 and EUV are not synchronized at all times and the calculated ionospheric delay with F10.7 might be greater than the actual delayed ionospheric response to EUV (Woods et al, 2005;Chen et al, 2018).…”
Section: Representation Of the Delay For Tec And Fof2mentioning
confidence: 66%
See 1 more Smart Citation
“…In earlier studies, the correlation of the ionospheric delay has been calculated for different ionospheric parameters based on daily and hourly resolutions, as shown in Table 1. For example, Jakowski et al (1991) used the solar radio flux index F10.7 and calculated a delay of 1-2 d. Jacobi et al (2016) confirmed this delay with satellite-based EUV-TEC measurements (Unglaub et al, 2011) and also calculated the ionospheric delay with EUV fluxes. The validation with EVE flux measurements was important because the solar rotation variations of F10.7 and EUV are not synchronized at all times and the calculated ionospheric delay with F10.7 might be greater than the actual delayed ionospheric response to EUV (Woods et al, 2005;Chen et al, 2018).…”
Section: Representation Of the Delay For Tec And Fof2mentioning
confidence: 66%
“…Delay (d) Solar flux parameter Ionospheric parameter Titheridge (1973) 1 F10.7 TEC Jakowski et al (1991) 1-2 F10.7 TEC Jakowski et al (2002) 1-3 F10.7 TEC Afraimovich et al (2008) 1.5-2.5 F10.7, EUV Global mean TEC Oinats et al (2008) 2-4 F10.7 NmF2, TEC Zhang and Holt (2008) 2-3 F10.7 Electron density Min et al (2009) 2 F10.7 Electron density, TEC Lee et al (2012) 1-2 F10.7 Electron density Jacobi et al (2016) 1-2 F10.7, EUV Global mean TEC Ren et al (2018) 1 EUV Electron density scaled ionosonde, since they cover different latitudes ranging from ≈ 38 to ≈ 70 • N. The dense coverage of GPS stations over Europe allows for good comparison with TEC data for these locations (Belehaki et al, 2015). An analysis of the Southern Hemisphere with the South African region would be preferred because of a similar longitude, but there are some time and data gaps, which prevented a reliable estimation of the delay for the available stations.…”
Section: Publicationmentioning
confidence: 99%
“…TEC is the vertically integrated electron density of the ionosphere which is usually given in TEC units (1 TECU = 10 16 electrons m −2 ). The ionospheric variability due to changes in solar activity has been studied extensively by various researchers (e.g., Jakowski et al, 1991;Rishbeth, 1993;Su et al, 1999;Forbes et al, 2000;Liu et al, 2006;Afraimovich et al, 2008;Lee et al, 2012;Jacobi et al, 2016, and references therein). Such studies are of great importance for improving our understanding of the solar influence on radio communication and navigation systems like Global Navigation Satellite Systems (GNSS).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to degradation of EUV measuring instruments solar proxies may be more suitable (BenMoussa et al, 2013), or repeated calibration is necessary. The availability of the direct EUV measurements provide an opportunity for comparing EUV with different solar proxies (e.g., Jacobi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation